call y = x^2 so x = +/- sqrt y
y^2 = 625
y = 25 or y = -25
x = sqrt 25 = +5 or -5
y = sqrt-25 = +5i or -5i
Any expression of the form a^2 - b^2 can be written as (a + b)(a - b).
Therefore, x^4 - 625) = (x^2 + 25)(x^2 - 25).
Then, (x^2 + 25)(x + 5)(x - 5)
Math - Rewrite the middle term as the sum of two terms and then factor ...
polynomials - lol, i also have these Factor the polynomial x2 + 3x – 18. Which ...
calculus - s=-4.9t²+245t+14.7 s=-4.9(t²-245/4.9t)+14.7 s=-4.9(t²-50t)+14.7 s=-4...
algebra 1 - Factor completely 36x2 + 60x + 25 Factor completely 4n2 + 28n + 49
math - Factor the following completely. x^2-12x+20
math - Completely factor the following expression: 16y2 – 25z2
Math - Please help with the following: Factor completely 3x^2-5x+1
math - I need help with these two problems please. Completely factor the ...
math - factor the following expression completely 75x^4+35x^3-10x^2
Math - Factor Completely the following Expression: 27X4 - 108 X2 the 4 is to the...